Soil-transmitted helminth infection and skin prick test reactivity in children - Lubis, Schenny Regina; lrsa, Lily; Evalina, Rita; Supriatmo, Supriatmo; Sjabaroeddin, M. (Paediatrica Indonesiana, 2014)
Background Allergic diseases cause an increasingly large burden in developed countries and in urban areas of middleincome countries . Paras itic infections may induce allergic responses in humans, particularly soil-transmitted helminth (STH) infections that are prevalent in childhood in developing countries. Although soil-transmitted helminth infec tions have been associated with lower prevalence of allergen skin test reactivity, study outcomes remain inconclusive. Objective To analyze for an association between STH infections and skin prick test reactivity in children. Methods We conducted a cross-sectional study in August 2009 among primary school students aged 7- 12 years, at Secanggang Subdistrict, Langkat District, North Sumatera Province. Sixty eight children were recruited in this study consisted of 34 children with STH infections and the other 34 children without any STH infection. Soil-transmitted helminth infections were determined by Kato-Katz stool examination s. All subjects underwent skin prick tests for seven allergens. Results were con sidered to be positive if wheal diameters 2: 3 mm and negative when wheal diameters < 3 mm. Data was an alysed by Chi-square test. Results Stool examinations revealed that the most common infec tion was T. trichiura (18/34 subjects), followed by mixed infections (T. trichiura and A lumbricoides; 12/34 subjects), and A. lumbricoides (4134 subjects). There was a significant association between STH infections and negative skin prick test (P= 0.002). In addition, there were significant associations with negative skin prick tests for each helminth type: A. lumbricoides (P=0.001) , T. trichiura (P=0.01) and mixed infection (P = 0.006). Severe infection intensity was also significantly associated with negative skin prick tests (P=0.031) . Conclusion Children with STH infections tend to have negative skin prick test results.